ELECTRON MICROSCOPIC PROPERTIES OF A NEW ANTIMICROBIAL NANODRUG BASED ON COPPER-CALCIUM HYDROXIDE COMPOUND - V.A. RUMYANTSEV; G.A. FROLOV; A.V. BLINOVA; YA .N. KARASENKOV; E.V. BITYUKOVA (Avicenna Tajik State Medical University, 2021)
Objective: To study the structural arrangement of the copper-calcium hydroxide (CCH), a commercially available dental paste used in aqueous suspension, as well as a new antimicrobial nanodrug based on CCH and a hydrosol of copper nanoparticles and copper (II) oxide. Methods: Dental paste Cupral® manufactured by "Humanchemie GmbH" (Germany) was investigated. Immediately prior to the study, it was diluted with either distilled water or a hydrosol of copper nanoparticles and copper (II) oxide in a ratio of 1:2. The hydrosol was obtained in the Department of Physical Chemistry laboratory at the National University of Science and Technology "MISiS", using the method of condensation of low-temperature plasma in a spark discharge. The microstructure of the obtained samples was analyzed using a transmission electron microscope (TEM), LEO 912 AB OMEGA (Carl Zeiss, Oberkochen, Germany). Results: Dilution of CCH with a hydrosol of copper nanoparticles and copper (II) oxide results in forming a complex nanosized composite structure. Nanoparticles in the dispersed phase penetrate the surface layers of CCH particles, which are crystalline hydrates of copper (II) oxide and calcium oxide. Conclusion: The discovered phenomenon could be helpful in the design of a new technology of nanoimpregnation of the tooth root dentin in endodontic and periodontal treatment, which does not require additional electrophoresis.